The effect of pretreatment powder using ball mill and ultrasound on the properties of single cell solid oxide fuel cell - Sulistyo, S.; Arifin, Saparudin; Mahzan, Shahruddin (Trans Tech Publications, 2013)
Solid oxide fuel cell (SOFC) is currently popular due to its capability to convert hydrogen into electricity directly from oxidizing hydrogen fuel. The SOFC is one of the expected renewable energy devices and green technology in the future because of less carbon dioxide production and no pollutant product. Performance of SOFC was influenced by morphology and microstructure of the material, starting particle size and particle’s distribution. This paper addresses the comparative evaluation of using pretreatment NiO/YSZ powder using ball mill and ultrasound processess on the performance of a single cell SOFC. The performance of solid oxide fuel cell was evaluated using scanning electron microscopy (SEM), X-Ray diffraction (XRD) and impedance spectroscopy, measured at room temperature. The results indicate that the treatment using ultrasound process is better than ball mill process due the total resistance is smaller and distribution particle is more homogenous.